Coronally Advanced Flap with Amniotic Membrane in the Treatment of Gingival Recession: Three Case Reports - Bolla, Vijayalakshmi (Int J Appl Basic Med Res, 2019)
Gingival recession is defined as an apical displacement of soft tissues to the cementoenamel junction. Various treatment options for the management of gingival recessions include laterally positioned flap, double papillae flap, coronally advanced flap (CAF) with or without guided tissue regeneration, free gingival autografts, and autogenous subepithelial connective tissue grafts. Three patients with multiple adjacent gingival recessions in the upper jaw were treated utilizing amniotic membrane (Tata memorial) with CAF. The results of this procedure show that amniotic membrane can be used in the treatment of gingival recession defects with significant root coverage and to increase the thickness of keratinized gingiva. There was an increase in height and thickness of keratinized gingiva from 3 to 3.5 mm and 1.5 to 2 mm, respectively. The present results suggest that the combined approach of CAF and amniotic membrane can be considered as a treatment option for multiple adjacent gingival recessions.